British Heart Rhythm Society Standards for Implantation and Follow-up of Cardiac Rhythm Management Devices in Adults: January 2024 Update - Paul Foley; Honey Thomas; Mark Dayer; Sophie Robinson; Vivienne Ezzatt; Matthew Swift; Nadiya Johal; Eleri Roberts (Arrhythmia & Electrophysiology Review)
This updated guidance is designed to help with implantation and follow-up with agreed standards of practice. The update includes new guidance on subcutaneous defibrillators, leadless pacemakers and conduction system pacing. It includes new guidance on considerations at the time of a potential box change and techniques to be considered to minimise the risk of infection.